Upper Jurassic (Oxfordian‒Tithonian) ammonites and biostratigraphy of the Spiti Shale Formation of the Spiti and Zanskar regions in the Indian Himalayas - Bhosale, Suraj; Pandey, Dhirendra; Alberti, Matthias; Fürsich, Franz; Chaskar, Ketan; Thakkar, Mahesh (Schweizerbart Science Publishers, 2024)
The Spiti Shale Formation in the Spiti and Zanskar regions of the Himalayas has yielded several ammonites collected systematically from ten localities. The ammonites from Zanskar are poorly preserved compared to those from Spiti due to intense tectonic activity. Nevertheless, the single specimen of Malagasites cf. subfrequens indicated the Tithonian age for the Rangdum section in Zanskar. In the Spiti area, 15 genera represented by 30 taxa have been identified, described and illustrated. The majority of the specimens belong to the subfamilies Paraboliceratinae, Virgatosphinctinae, and Himalayitinae. Taramelliceratinae, Streblitinae, and Berriasellinae are less common, whereas Mayaitinae are particularly rare. The oldest ammonites were collected from Oxfordian strata around Chichim and Langza section (Spiti region) and identified as Mayaites and Epimayaites. The Kimmeridgian strata is either absent/not exposed or insignificant and require future work. The base of the Lower Tithonian is marked by Kossmatia, which co-occurs with Paraboliceras, Metauhligites, Nepalites, Uhligites, Aulacosphinctoides and Indodichotomoceras biplicatus. This record is succeeded by Virgatosphinctes and Malagasites. The Upper Tithonian is marked by Aulacosphinctes mainly recorded from the Demul area (Spiti region). The majority of Upper Tithonian in the Spiti region is characterized by Aulacosphinctes, Paraboliceras Himalayites, and Blanfordiceras. The record of ammonite taxa from the present study reveals low taxonomic biodiversity in the Spiti Shale Formation.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Ammonites; biostratigraphy; India; Jurassic; taxonomy